Oxygen Is an Ambivalent Factor for the Differentiation of Human Pluripotent Stem Cells in Cardiac 2D Monolayer and 3D Cardiac Spheroids - Souidi, Monia; Sleiman, Yvonne; Acimovic, Ivana; Pribyl, Jan; Charrabi, Azzouz; Baecker, Volker; Scheuermann, Valerie; Pesl, Martin; Jelinkova, Sarka; Skladal, Petr; Dvorak, Petr; Lacampagne, Alain; et al. (International journal of molecular sciences, 2021)
Numerous protocols of cardiac differentiation have been established by essentially focusing on specific growth factors on human pluripotent stem cell (hPSC) differentiation efficiency. However, the optimal environmental factors to obtain cardiac myocytes in network are still unclear. The mesoderm germ layer differentiation is known to be enhanced by low oxygen exposure. Here, we hypothesized that low oxygen exposure enhances the molecular and functional maturity of the cardiomyocytes. We aimed at comparing the molecular and functional consequences of low (5% O2 or LOE) and high oxygen exposure (21% O2 or HOE) on cardiac differentiation of hPSCs in 2D- and 3D-based protocols. hPSC-CMs were differentiated through both the 2D (monolayer) and 3D (embryoid body) protocols using several lines. Cardiac marker expression and cell morphology were assessed. The mitochondrial localization and metabolic properties were evaluated. The intracellular Ca2+ handling and contractile properties were also monitored. The 2D cardiac monolayer can only be differentiated in HOE. The 3D cardiac spheroids containing hPSC-CMs in LOE further exhibited cardiac markers, hypertrophy, steadier SR Ca2+ release properties revealing a better SR Ca2+ handling, and enhanced contractile force. Preserved distribution of mitochondria and similar oxygen consumption by the mitochondrial respiratory chain complexes were also observed. Our results brought evidences that LOE is moderately beneficial for the 3D cardiac spheroids with hPSC-CMs exhibiting further maturity. In contrast, the 2D cardiac monolayers strictly require HOE.
Keywords: buněčná diferenciace; buněčné sféroidy; Calcium; Sarcoplasmic Reticulum; exprese genu; Humans; Pluripotent Stem Cells; Gene Expression; contractile properties; pluripotentní kmenové buňky; Mitochondria, Heart; kardiomyocyty; 2D-monolayer; vápník; hPSC-derived cardiomyocytes; cardiac spheroids; srdeční mitochondrie; lidé; Biomarkers; Myocytes, Cardiac; Oxygen; Spheroids, Cellular; kyslík; biologické markery; Cell Differentiation; intracellular calcium handling; oxygen exposure; Cell Culture Techniques; sarkoplazmatické retikulum; mitochondrial oxygen consumption; embryoid bodies; buněčné kultury